Microplastics: Global occurrence, impact, characteristics and sorting - Prabhu, Prathiksha P.; Pan, Koustav; Krishnan, Jegatha Nambi (Frontiers in Marine Science, 2022)
Stressors like microplastics (MPs) cause proliferating environmental pollution globally. Since plastics are continuously introduced into water bodies through numerous paths, novel solutions are required to segregate as well as decline their quantity in various environmental sectors. Numerous techniques have been used and proposed in the last 10 years to screen and enumerate MPs, define the particle’s properties, for instance form, color, or size, and recognize the polymer material. This critical review aims to provide an overview of advanced procedures in MP investigation, provides illustrations of probable routes forward and lingering challenges, and categorizes present approaches as per their underlying research question. Methods presently employed for MP sampling, extraction, identification, characterization, and quantification were evaluated. Studies proposing use of precursors for removal of MPs from water via the sol–gel process were reviewed. Research on microfluidics systems finds application in environmental and industrial fields and has gained momentum in concentrating, sorting, classifying, focusing, and desegregating MPs. This review briefly discusses active and passive label-free microfluidic methods that are efficient in executing the desired particle separation and are gaining momentum in the ecological analysis of MPs. Although some sets of preliminary data of MPs at selected regions across the globe have been studied and obtained, the degree of MP contamination in most important rivers, nearshore inland areas, and air is yet to be understood completely. Along the Charleston Harbor Estuary, the MP concentration in intertidal sediment was found to be 0 to 652 MPs/m2. In Asia, at the South Korean region, western Pacific Ocean, a high plastic concentration of 15–9,400 particles/m3 was reported. In India, the MP concentration was identified as 288 pieces/m3 in the Netravati River. In Turkey, ingestion of MPs was reported to be found in 458 out of 1,337 fish samples, indicating the polluted situation of the Mediterranean Sea. Despite the rapid development in MP analysis, no standardized technique for sampling along with separation has been approved. Therefore, for attaining a more inclusive picture of MPs’ fate and abundance, this study highlights the importance of a standardized procedure for MP research that can be used globally and adequately enables comparisons around the world.